THE IMPACT OF STOCK MARKET FLUCTUATIONS ON THE MENTAL AND PHYSICAL WELL‐BEING OF CHILDREN. - Cotti, Chad; Simon, David (Economic Inquiry, 2018)
The stock market crash of 2008 caused a severe impact to households. Earlier research has explored the impacts of a stock market crash on life well‐being, psychological stress, and adult health behaviors. We extend this literature by documenting impacts of stock market fluctuations on a range of child outcomes; including effects on both mental and physical health. We show a negative effect of a market crash on hospitalizations, child reported health status, sick days from school, and an aggregate health index measure. Both graphical and regression‐based analysis reveal that our results are not driven by a preexisting trend of declining child health before the market crash and extensive sensitivity analysis demonstrates that the results are robust to multiple empirical specifications. (JEL I15, E32, J13)